The Students' Weaknesses in Solving the Problems Related to Mathematics Literacy - Dani Kusuma; Y. L. Sukestiyarno; Wardono Wardono; Adi Nur Cahyono (International Conference on Science, Education, and Technology, 2021)
Literacy ability is the ability to formulate, apply, and interpret daily life problems into mathematical form. In this case, mathematical literacy is an ability that needs be mastered by the students. The purpose of this study is to investigate the weaknesses of the students in solving problems related to mathematical literacy. This research is a descriptive qualitative research by using triangulation in conducting data analysis. The triangulation refers to the triangulation between the results of student work, interviews, and observations. The subjects in this study are 15-years old students. Then, the instruments used in the study are mathematical literacy tests, interview guidelines and observation guidelines. The results show that in the process of solving the mathematical literacy problems, students experience difficulties in the process of understanding the problem in mathematical form, known as mathematising. Therefore, the obstacles in the mathematising process result in students' ability to complete the next stage. The problems found from the research show that students are less familiar with literacy-based questions so that they have difficulty in the process of understanding